Synthesis of zinc phthalocyanine derivatives for possible use in photodynamic therapy - Matlaba, Pulane Maseleka (Rhodes University, Faculty of Science, Department of Chemistry, 2003)
The synthesis of symmetrically and unsymmetrically substituted zinc phthalocyanines (ZnPc) derivatives is done according to reported procedures. The unsymmetrical ZnPc derivatives are synthesized by ring expansion of sub-phthalocyanine complexes. Ring substitution is effected with tert-butyl phenol, naphthol, and hydroxybenzoic acid. Comparison of the redox potentials for the complexes substituted with varying numbers of tert-butyl phenol: 1, 2, 3, 6 and 8 show that the complex with the highest number of substituents are more difficult to oxidize and easier to reduce. Water soluble sulphonated ZnPc (ZnPcSn) was prepared. The possibility of using axial ligation to increase the solubility and the photochemical activity of sulphotnated ZnPc in aqueous solutions was investigated. Pyridine, aminopyridyl and bipyridyl were used as axial ligands. When bipyridyl was used as the axial ligand, solubility of the ZnPcSn increased, shown by the increase in the Q-band of the monomer species in solution and the singlet oxygen quantum yields was relatively higher than that of the unligated ZnPcSn. The singlet oxygen quantum yields by the various complexes in DMF using diphenylisobenzofuran as a chemical quencher for organic solvent were determined. Singlet oxygen quantum yields for the unsymmetrically ring substituted complexes range from 0.22 to 0.68. Photobleaching quantum yields are in the order of 10-5, which means that the complexes are relatively photostable.
Keywords: Photochemotherapy; Electrochemistry; Phthalocyanines; Zinc